Antibacterial mechanism of apple phloretin on physiological and morphological properties of Listeria monocytogenes - ZHAO,Pengtao (2022)
Abstract Green bactericides are excellent strategies for reducing food spoilage. Phloretin was regarded as efficient, broad-spectrum and safe preservative, which showed enormous potential in food industry. Inhibitory mechanism of phloretin on Listeria monocytogenes was systematically elucidated through integrity of cell membrane, intracellular protein content, energy level, and nucleic acid morphological character. SEM and TEM results showed minimal injury of cell membrane, which was further proved by a leakage of potassium ions, ATP and little protein and nucleic acid. There were drastic reduction of intracellular or total protein and ATP compared to cell without phloretin treatment. However, the specific activity of hexokinase and isocitrate dehydrogenase were unaffected after phloretin treatment. From these results, we concluded that phloretin’s bacteriostatic mechanism is decreasing the intracellular protein content and energy level resulting from DNA aggregation. This finding was prospective to fully illustrate the phloretin’s mechanism and develop it into a natural preservative in food industry.